Projections of single-level indirect lumbar interbody fusion volume and associated costs for Medicare patients to 2050 - Kyle A. Mani, BS; Samuel N. Goldman, BS; Noel Akioyamen, MD; Emily Kleinbart, BS; Yaroslav Gelfand, MD; Saikiran Murthy, DO; Jonathan Krystal, MD; Ananth Eleswarapu, MD; Reza Yassari, MD; Mitchell S. Fourman, MD, MPhil (North American Spine Society Journal, 2025)
ABSTRACT: Background: Anterior, Oblique, and Lateral Lumbar Interbody Fusions (ALIF/OLIF/LLIF) are powerful modalities for achieving indirect decompression of lumbar foraminal stenosis while providing a large fusion surface and preserving the posterior vertebral structures. This study aimed to project future trends in the implementation rates and associated costs of ALIF/OLIF/LLIF in Medicare patients aged >65 in the US. Methods: Data was acquired from the Centers for Medicare and Medicaid Services (CMS) from January 1, 2000 to December 31, 2022, using CPT codes to identify ALIF/OLIF/LLIF procedures. The Prophet machine learning algorithm, using Bayesian Inference, was applied to data from 2000 to 2019 to generate point forecasts for 2020 to 2050 with 95% forecast intervals (FIs). Predictive performance was evaluated by splitting the data into training (75%) and validation (25%) sets, and calculating normalized root mean square error (NRMSE). Sensitivity analyses were conducted by comparing Prophet's projections with those from Linear and Log-linear Ordinary Linear Squares, Poisson, Negative-Binomial, and ARIMA models. Compound annual growth rates (CAGRs) were calculated to assess prior and future trends in procedural volume and costs from 2000 to 2050. CMS procedure counts were adjusted for Medicare Advantage patients using Kaiser Family Foundation data and costs were adjusted for inflation using the U.S. Consumer Price Index. Alternative volume projections were provided to account for the (I) impact of COVID-19 and (II) future expenditure limits using the 2022 to 2031 CMS National Health Expenditure report. Results: Between 2000 and 2019, the adjusted annual ALIF/OLIF/LLIF volume increased from 5,093 to 45,758 cases, with a CAGR of 12.32%. The total adjusted cost for these procedures increased from $7,750,692 to $43,531,555, with a CAGR of 9.62%. During the same period, the mean inflation-adjusted reimbursement for ALIF/OLIF/LLIFs 37.8% from $1,194.86 to $743.21 per procedure. Based on Prophet model analysis, projections estimate that procedural volume and total cost will increase by 17.8% and 14.8%, respectively, for each 5-year period from 2020 to 2050. The COVID-19 pandemic caused a 2.9% decrease in ALIF/OLIF/LLIF procedural volume in 2020 compared to 2019, but volume recovered by 2022, increasing by 1.4% from prepandemic levels. By 2050, procedural volume accounting for COVID-19 reflects a 23.5% reduction compared to estimates that did not factor in COVID-19. The Prophet model demonstrated the best predictive performance, with NRMSE values of 0.0619 for volume and 0.0507 for costs. Conclusions: Large increases in the utilization and costs of ALIF/OLIF/LLIF are anticipated through 2050. By 2030, the estimated carrying capacity for ALIF/OLIF/LLIF expenditures is projected to reach approximately $75.6 million, constrained by CMS expenditure limits and market size. Prophet model projections indicate that expenditures for ALIF/OLIF/LLIF are expected to exceed this cap by the end of the decade.